Hourly CO2 emission assessment of a 5 MWth centralized groundwater HP district heating system in Geneva. (November 2019) - Schneider, Stefan; Santandrea, Dario; Romano, Elliot; Hollmuller, Pierre
Abstract: In the present paper, we develop an hourly simulation model for determination of the relevant system load curves of a new district of 30 high performance multi-family buildings (163'00 m2 heated floor area) situated in Geneva, which is equipped with a 5 MWth groundwater HP. As a complement, at building level, heat recovery on exhaust air is used for pre-heating of DHW by way of decentralized air-to-water HPs. As a result of our model, the 10.7 GWh annual heat production (65% for SH, 35% for DHW) should require 1.93 GWh HP electricity (85% centralized, 15% decentralized). When crossing the corresponding profile with a recent analysis of the hourly CO2 content of the Swiss electricity mix, the annual carbon content of heat amounts to 47 gCO2 /kWhth ., which is 4 times less than with a centralized gas boiler.